Woodcutting Activities in Tabuk Region (Saudi Arabia): Assessment of Conservation Knowledge - Khalid A. Al-Mutairi; Adnan Al-Atawi; Abdulmajeed Alajlan; Salman A. Al-Shami (Aceh International Journal of Science and Technology, 2015)
The present study aims to investigate the effect of different social factors on the woodcutting frequency in Tabuk Region. A total of 100 people participated in this study by answering the questionnaire questions. The conservation knowledge of the participants was also assessed through 4 questions (Yes or No). The final score of the conservation knowledge assessment is 4. The present study findings showed that most of people like to cut the wood for heating during winter and fall seasons. The frequency of woodcutting in Tabuk Region was once a month. Among the social factors involved in this study, education showed negative and significant relationship with the number of logging times. However, age had positive relationship with the number of logging times. The most favourbale species to be cut and used for heating and cooking in Tabuk are; Acacia tortilis, Acacia ehrenbergiana, Retama reaetam and Calligonum comosum. For the assessment of the public conservation knowledge, it was found that most of participants had moderate to good conservation knowledge as most of them answered 3 questions correctly out of 4. The conservation knowledge showed to be affected positively by education level and negatively by the number of family members. In conclusion, it was found that there is remarkable woodcutting stress on wild plants in Tabuk Region and immediate and effective actions should be performed